2010
DOI: 10.1520/gtj102326
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Resistivity and Time Domain Reflectometry Sensors for Assessing Moisture Content in Bioreactor Landfills

Abstract: Instruments that can monitor the in situ moisture content of landfilled waste would be of great benefit to landfill operators, especially those operating their facilities as bioreactor landills (wet landfills). Two instrumentation technologies for measuring in situ moisture content (resistivity sensors and time domain reflectometry (TDR)) in landfills were examined and compared. Resistivity and TDR instruments were installed in close proximity at multiple locations in a leachate recirculation well field at a b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…They have found that debris flow was separated when it went through a barrier, and the barrier's position and rotation angle could change the deposition areas. Time domain reflectometry (TDR) is an electrical measurement technique used to determine the spatial location and nature of various objects (Robert 2009;Suits et al 2010;Ragni et al 2012). Research on the use of the TDR detection technology in monitoring geological disasters began in the mid-1990s (Dowding and Pierce 1994).…”
Section: Introductionmentioning
confidence: 99%
“…They have found that debris flow was separated when it went through a barrier, and the barrier's position and rotation angle could change the deposition areas. Time domain reflectometry (TDR) is an electrical measurement technique used to determine the spatial location and nature of various objects (Robert 2009;Suits et al 2010;Ragni et al 2012). Research on the use of the TDR detection technology in monitoring geological disasters began in the mid-1990s (Dowding and Pierce 1994).…”
Section: Introductionmentioning
confidence: 99%